Synthesis and solid state structure of pyridyl diboroxines linked by a chiral spacer analogous to Tröger's base. Issue 2 (8th January 2015) - Elsegood, Mark R.J.; Kimber, Marc C.
Graphical abstract: Abstract: Pyridyl-assisted templating of phenyl boronic acid has been utilised to link two remote boroxines via a chiral spacer. The chiral spacer is a carbocyclic analogue of Tröger's base and contains a unique chiral cavity, and the flanking boroxine units have been shown, by single crystal X-ray analysis, to extend the size and shape of this cavity.